2020
DOI: 10.30773/pi.2020.0306
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Change in Plasma Clozapine/N-desmethylclozapine Ratio with Cognitive Performance in Patients with Schizophrenia

Abstract: Objective The clozapine/N-desmethylclozapine (NDMC) ratio is proposed to be used as a predictor of cognitive performance in clozapine-treated patients, as its principal metabolite, NDMC, has an opposite action with clozapine on the cholinergic system. The aim of this study is to determine whether clozapine has influence on cognitive performance in accordance with changes in the clozapine/NDMC in patients with schizophrenia.Methods The data of fifteen patients with schizophrenia, who had initial and follow-up a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…Furthermore, recent studies found that the ratio of clozapine to its active metabolite norclozapine (N-Desmethylclozapine) in plasma is associated with patients' cognitive performance. Clozapine has different pharmacodynamic properties and affinity to cholinergic, dopaminergic, and serotonergic receptors compared to its active metabolite and literature supports that lower clozapine/norclozapine ratios in clinically stable patients are associated with better cognitive outcome ( 63 , 64 ). The metabolism of clozapine to norclozapine is induced by P450 enzymatic system and thus adjunctive treatments, caffeine consumption, smoking, and other factors such as age, race, and gender may alter this ratio between individuals ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies found that the ratio of clozapine to its active metabolite norclozapine (N-Desmethylclozapine) in plasma is associated with patients' cognitive performance. Clozapine has different pharmacodynamic properties and affinity to cholinergic, dopaminergic, and serotonergic receptors compared to its active metabolite and literature supports that lower clozapine/norclozapine ratios in clinically stable patients are associated with better cognitive outcome ( 63 , 64 ). The metabolism of clozapine to norclozapine is induced by P450 enzymatic system and thus adjunctive treatments, caffeine consumption, smoking, and other factors such as age, race, and gender may alter this ratio between individuals ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of clozapine, lower clozapine to N-desmethylclozapine (NDMC) plasma concentration ratios are associated with better cognitive functioning in several observational studies, possibly due to a differential effect of the parent drug and its metabolite on muscarinic receptors. [40][41][42][43][44] However, these findings have not been universally consistent. 45 Furthermore, clozapine:NDMC plasma ratios may not currently be reliable enough for clinical decision making.…”
Section: Case 1: Ciasmentioning
confidence: 96%
“…[41] Effectiveness of FGAs vs. SGAs on cognition and life quality of schizophrenia patients N = 114 (78 men and 36 women) Age range 18-65 years old [42] Cognitive effects of the treatment with injectable vs. oral risperidone for schizophrenia patients N = 30 [43] Association between cognitive improvement and clozapine treatment in schizophrenia patients N = 15 Age range >19 years old [44] Long term effects of discontinuing the antipsychotic treatment of schizophrenia patients N = 178 (80 men and 98 women) Age range 18-65 years old [45] Social cognition mediates the relationship between neurocognitive functions and negative symptoms N = 208 [46] Risperidone vs. olanzapine vs. aripiprazole in acute schizophrenia at 6/12 months of treatment N = 546 [47] Ziprasidone treatment changes in functional and structural brain hemisphere responsible for cognitive functioning N = 45 CBD-cannabidiol; CTRS-clozapine-resistant treatment-refractory schizophrenia; FGAs-first-generation antipsychotics; SGAs-second-generation antipsychotics.…”
Section: Authors Aim Of the Study Participantsmentioning
confidence: 99%